Volume 5: 37th Design Automation Conference, Parts a and B 2011
DOI: 10.1115/detc2011-47437
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Residual Stresses in Brake Discs by Metamodeling

Abstract: During casting residual stresses are developed due to the solidification and cooling. In this work the robustness of residual stresses in casted brake discs with respect to variations in four parameters is evaluated. The parameters are Young’s modulus, yield strength and hardening, time of breaking the mould and the thickness of the brake disc. The robustness analysis is performed by Monte Carlo simulations of metamodels which are surrogates to a finite element model. Quadratic response surfaces and Kriging ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Shin et al [90] also showed that a non heat-treated disc when exposed to a high temperature experiences run out which is more than twice the run out experienced by a heat-treated disc. In another study, Hofwing [91] showed with numerical simulations that residual stresses exist after casting and machining of the disc.…”
Section: Disc Runoutmentioning
confidence: 99%
“…Shin et al [90] also showed that a non heat-treated disc when exposed to a high temperature experiences run out which is more than twice the run out experienced by a heat-treated disc. In another study, Hofwing [91] showed with numerical simulations that residual stresses exist after casting and machining of the disc.…”
Section: Disc Runoutmentioning
confidence: 99%
“…It outperforms other surrogate modeling techniques due to its unique characteristics of spatiotemporal modeling. In particular, regarding materials forming, a lot of research based on kriging model technique has been conducted (e.g., [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]). Tuo et al [ 24 ] proposed a kriging model based on a nonstationary Gaussian process that integrates the outputs of different mesh densities in finite element analysis and provides approximation to the exact solution, and then applied the model in casting simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Tuo et al [ 24 ] proposed a kriging model based on a nonstationary Gaussian process that integrates the outputs of different mesh densities in finite element analysis and provides approximation to the exact solution, and then applied the model in casting simulation. Hofwing et al [ 25 ] performed the robustness analysis of residual stresses in the brake discs casting by Monte Carlo simulations of metamodels, considering quadratic response surfaces and kriging approximations. Li et al [ 26 ] presented a hybrid inverse identification approach by combining the finite element method, kriging model, Latin hypercube sampling and multi-island genetic algorithm to deal with material parameters of aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%